Settler Colonialism and the Policing of Idle No More - Crosby, Andrew C. (Social justice, 2016)
Idle No More is a grassroots movement that presents a powerful politics of resistance to settler colonialism. In response, security agencies in Canada have categorized the movement as both a criminal and a national security threat. This article is focused on the policing and surveillance of Idle No More by security agencies in Canada. In detailing the extensive surveillance of the movement, we describe the policing of Idle No More as a continuation of colonial policing practices that target—with the objective of eliminating—indigenous movements that challenge the legitimacy of the settler state.